Nitric oxide and endothelin relationship in intestinal ischemia/reperfusion injury - DAĞLI, EMRULLAH TOLGA; HAKLAR, GONCAGÜL; YÜKSEL, MERAL (My University, 1998)
Gastrointestinal mucosal blood flow is dependent on a balanced release of vasoactive substances from endothelium. Nitric oxide (NO) may increase the flow by vasodilatation and/or antiaggregation whereas endothelin (ET) may decrease it by vasoconstriction and aggregation. NO and ET may have counterbalancing effects on each other in tissue damage. In order to test this hypothesis, in this study on rats, L-arginine to increase NO levels and N(G)-nitro-L-arginine methyl esther (L-NAME) to decrease NO levels have been used in an intestinal ischemia/ reperfusion (I/R) injury model and portal vein ET response was evaluated. Lipid peroxidation product measurements and chemiluminescence (CL) studies were also carried out in ileal tissue samples. Intestinal I/R injury caused an increase in portal venous ET levels with levels of 9.4+/-0.5 fmol/ml in sham operation and 14.8+/-1.6 fmol/ml in I/R group. ET level of L-NAME-sh group was lower than that of sham-operated group and also ET level of L-NAME-I/R group was lower than that of I/R group. This yielded the conclusion that inhibition of NO synthesis decreases portal venous ET levels in this model. Increased NO production by L-arginine caused increased ET levels in sham operated groups but this effect was not observed in I/R injury state. This study also showed that inhibition of NO synthesis has a protective role by reducing the reperfusion damage in this model. It is likely that NO and ET have a feedback effect on each other both under physiologic conditions and I/R injury.
Keywords: Female; Animals; Rats; Rats, Wistar; Lipid Peroxidation; Luminescent Measurements; Intestinal Mucosa; Nitric Oxide; Reperfusion Injury; Arginine; Enzyme Inhibitors; NG-Nitroarginine Methyl Ester; Endothelins